Reversible Binding of the HPLC6 Isoform of Type I Antifreeze Proteins to Ice Surfaces and the Antifreeze Mechanism Studied by Multiple Quantum Filtering−Spin Exchange NMR Experiment - Ba, Yong; Wongskhaluang, Jeff; Li, Jiabo (Journal of the American Chemical Society, 2003)
Antifreeze proteins (AFPs) protect organisms from freezing damage by inhibiting the growth of seed-ice crystals. It has long been hypothesized that irreversible binding of AFPs to ice surfaces is responsible for inhibiting the growth of seed-ice crystals as such a mechanism supports the popularly accepted Kelvin effect for the explanation of local freezing-point depression. However, whether the binding is reversible or irreversible is still under debate due to the lack of direct experimental evidence. Here, we report the first direct experimental result, by using the newly developed multiple quantum (MQ) filtering−spin exchange NMR experiment, that shows that the binding of HPLC6 peptides to ice surfaces is reversible. It was found that the reversible process can be explained by the model of monolayer adsorption. These results suggest that the Kelvin effect is not suitable for explaining the antifreeze mechanism, and direct interactions between the peptides and the ice-surface binding sites are the driving forces for the binding of AFPs to ice surfaces. We propose that there exists a concentration gradient of AFP from an ice-binding surface to the solution due to the affinity of ice surfaces to AFPs. This concentration gradient creates a dense layer of AFP in contact with the ice-binding surface, which depresses the local freezing point because of the colligative property, but not the Kelvin effect.